Ni/Al2O3/Foam Electric Heating Catalyst: Mitigating Carbon Emissions and Enhancing Reactor Temperature Uniformity - Yanlun Ren; Li Zhang; Hong Xu (Energies)
Substituting the traditional fuel combustion heating mode in hydrogen production reactors with electric heating demonstrates a significant potential for reducing carbon dioxide emissions. An Ni/Al2O3/Ceramic Foam Electric Heating Catalyst was created using a replication template method and a slurry method. On a reactor with dimensions of Φ25 × 800 mm, the differences in the heating rate, axial temperature variance, radial temperature variance, and energy consumption between internal and external heating were analyzed. The results show that: (1) By optimizing the structure of the electric heating wires, the temperature uniformity in the catalyst is enhanced; (2) At 650 °C, 3000 h−1, and S/C = 3, compared to traditional granular catalysts, the internal electric heating reduces the axial temperature variance by 69.4% and the radial temperature variance by 95%; and (3) Achieving a temperature of 650 °C using electric heating only requires 23 min, resulting in a 56.82% reduction in energy consumption compared to external heating.